THE TOBACCO INSTITUTE 1992 BUDGET PUBLIC AFFAIRS DIVISION COST CENTER SCIENTIFIC AFFAIRS NO. 1302 (Tufts Archival Research Center, 2007)
Confidential; Tobacco Institute budget for 1992. Contains the 1991 estimated and actual budget and the 1992 budget.